Tahirli, Zeyneb - (:unkn) unknown (My University, 2026)
Zeynab Tahirli Ilgar was born on February 13, 1993, in Baku, Azerbaijan. She completed her secondary education at Secondary School No. 54 named after A. Shaig in the Nasimi District of Baku, graduating in 2010. In the same year, she enrolled in the Faculty of Architecture and Design at Kocaeli University (Türkiye), where she studied Interior Design and received her Bachelor's degree in 2015. She continued her education at the same university, earning a Master's degree in Interior Design in 2023. Following her graduation, she worked as an Architect and Interior Designer at Körpü-Bina-Tikinti LLC. She later contributed to the ADA University projects while working at Gravity LLC until 2019. Since 2024, she has been serving as an Assistant Lecturer at the Azerbaijan University of Architecture and Construction. Alongside her academic career, she continues her professional practice as a freelance interior designer. She is the author of numerous interior design projects and has published a number of scientific articles and conference papers in the field of interior design. Through her teaching activities, she shares her professional knowledge and practical experience with university students, particularly in the area of interior design project development. Her academic and professional interests focus on interior architecture and design, combining research, creative practice, and education. She is committed to contributing to the advancement of the discipline through innovative design approaches, scholarly research, and the education of future professionals.